Penurunan Osteoclast Epifysis Tulang Radius Mencit Perimenopause dengan Pemberian Estrogen dan Berenang (OSTEOCLAST COUNT DECREASING ON EPIPHYSIS PART OF RADIUS IN PERIMENOPAUSAL MICE ON ESTROGEN AND SWIMMING TREATMENT) - ., Yuliana; Wiryanthini, Ida Ayu Dewi; Karmaya, Nyoman Mangku; Widarsa, Tangking (Jurnal Veteriner; Vol 13 No 4 (2012), 2013)
Increasing of life age expectancy has risen many health problem. One of the problem is osteoporosis.This disease can be prevented by estrogen and swimming treatment. Estrogen is not safe to be given inlong term. This study aim was to investigate the decreasing of osteoclast count in estrogen and swimmingtreatment. This study uded Pretest-Posttest Control Group Design with fifty two mice (15-16 months old).The mice were divided randomly into 4 groups, i.e. control, estrogen, swimming and combination group.After 90 days treatment, epiphysis of radius bone was sectioned and stained by haematoxyllin eosin.Osteoclast difference between groups were analyzed by using analysis of variance. Mean of osteoclast incontrol group was 0.12±0.1, and three other groups had the same level, i.e. 0,02±0,06. In conclusion, thedecrease of osteoclast count did not have any significant difference between treatment groups.
Keywords: osteoporosis, osteoclast, perimenopause, estrogen, swimming